2009
DOI: 10.1590/s1519-38292009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação do protocolo do "Projeto Nascer Maternidades" em uma maternidade de referência em Feira de Santana, Bahia, Brasil

Abstract: Objectives: to analyze the implementation of the N a s c e r M a t e r n i d a d e s P ro j e c t p ro t o c o l , a g u i d e l i n e f ro m t h e B r a z i l i a n M i n i s t r y o f H e a l t h f o r p ro p h ylactic/therapeutic measures on delivery for pregnant w o m e n w h o s e s e ro l o g i c a l s t a t u s v i s -à -v i s syphilis/HIV was unknown in the first Prophylactic measures for HIV were taken on delivery in the case of HIV-infected women. Eighty percent of t h e V D R L p o s i t i v e w o m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…In the city of Campos, Rio de Janeiro state, a study of pregnant women with syphilis found that the majority of the partners were not treated, the main justification being a nonreactive VDRL result. 27 This situation is highlighted in other studies which evidence pregnant women and partners with syphilis being managed improperly, especially with regard to treatment, 16,[27][28] and the lack of reception and guidance for the sexual partners. 18 The majority of the professionals demonstrated knowledge of the periods for the realiza-tion of the VDRL tests in pregnancy, stating that it should occur in the first and third trimesters (75.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the city of Campos, Rio de Janeiro state, a study of pregnant women with syphilis found that the majority of the partners were not treated, the main justification being a nonreactive VDRL result. 27 This situation is highlighted in other studies which evidence pregnant women and partners with syphilis being managed improperly, especially with regard to treatment, 16,[27][28] and the lack of reception and guidance for the sexual partners. 18 The majority of the professionals demonstrated knowledge of the periods for the realiza-tion of the VDRL tests in pregnancy, stating that it should occur in the first and third trimesters (75.8%).…”
Section: Discussionmentioning
confidence: 99%
“…18 The majority of the professionals demonstrated knowledge of the periods for the realiza-tion of the VDRL tests in pregnancy, stating that it should occur in the first and third trimesters (75.8%). However, studies show low coverage of VDRL testing, 12,16,23,28 or its performance only once during the prenatal period, with a considerable number of cases of women who are not reevaluated in the third trimester. 3,12,27 It is possible that this low covering of syphilis testing in pregnant women could also be related to the limitations imposed by the healthcare services, which in some places do not make the screening test available or do not return the result within an appropriate amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Oportunidades perdidas de diagnóstico precoce na gestação têm sido uma constante, identificadas em investigações nacionais 20-23 e regionais. 13,[24][25][26][27] No Rio de Janeiro, dados de 2000 mostraram que 25% das gestantes não realizaram exame anti-HIV no pré-natal, 24 enquanto dados colhidos entre 2007 e 2008 revelaram ausência do resultado deste exame em 26% dos cartões de pré-natal das gestantes com mais de 37 semanas gestacionais. 13 Se utilizarmos a informação dos prontuários, houve certa piora do indicador, mas se nos basearmos na informação materna, reduziu-se o percentual de mulheres sem o exame.…”
Section: Tabelaunclassified
“…No entanto, de acordo com os dados do prontuário, ocorreram apenas 2,2% de oportunidades perdidas de submissão ao teste rápido anti-HIV, representando um avanço em relação a estudos anteriores, pois para esta informação no âmbito hospitalar, o registro em prontuário é considerado como o padrão ouro. Em Feira de Santana entre 2003 e 2004, 26 82,3% das gestantes não testadas no prénatal deixaram de ser submetidas ao teste rápido anti-HIV, em Recife, na mesma época, este percentual foi de 15,5% 29 e no estudo "Sentinela-Parturiente", de âmbito nacional, 18% das mulheres não haviam sido testadas para o HIV durante a gestação e na maternidade. 22 A discordância entre as informações do prontuário e das mães sugere que este avanço na redução das oportunidades perdidas de testagem rápida não apresentou correspondência com a interpelação das mulheres pela equipe de saúde.…”
Section: Tabelaunclassified
See 1 more Smart Citation